Urban Planning and Disasters: A Systematic Review PRISMA - Santos, Rafaela Pastoura; Cortese, Tatiana Tucunduva P. (National Journal of City Management, 2022)
Climate change is already witnessed today, future forecasts continue to warn us about the possible impacts of our actions in the short and long term. With an increase in extreme events and the population living in urban centers, more and more cities will experience the effects of disasters. Although there are policies aimed at dealing with disasters, we know that the current measures are not enough to minimize this scenario. To better understand the relationship between urban planning and disasters, this article carries out a Systematic, based on PRISMA. The methodology allows the analysis of the literature with greater rigor, transparency, and the possibility of replication. For this study, articles in English were considered, with the following terms: disaster, disaster risk reduction, hazard mitigation, urban planning, and master plan. The main findings of this review show us that good urban planning, guided by resilience and risk management, with broad social participation, can act in reducing vulnerability, risks, and the impact of disasters in cities.